Self-limited conversion of MoO2 into ultramicro MoS2 nanosheets on graphene/CNTs matrix for hydrogen evolution with excellent stability. Issue 6 (7th April 2020) - Tian, Jingyang; Li, Jiaxin; Feng, Anlin; Han, Xinran; Lv, Yuancai; Ma, Mingyang; Lin, Chong
Abstract : Ultramicro MoS2 nanosheets with abundant active sites were uniformly dispersed in rGO, which can be effectively separated by CNTs. Abstract : Current research on MoS2 /graphene hybrids for the hydrogen evolution reaction (HER) reveals that there is still a huge challenge due to restacking and the scarcity of active sites. In this work, ultramicro MoS2 nanosheets with good dispersion and rich active sites are vertically grown on graphene via a self-limited growth strategy (S–MoS2 ). Moreover, carbon nanotube (CNT) scaffolds can effectively limit the restacking of graphene and MoS2, accelerating the transport of electrons and electrolytes. The synergism among the multi-function structures and composition control can improve the electrochemical HER activity. The obtained S–MoS2 /rGO/CNTs exhibits a low overpotential of 159 mV ( vs. RHE) at 10 mA cm −2 and a small Tafel slope of 85 mV dec −1 in 0.5 M H2 SO4 . Moreover, the S–MoS2 /rGO/CNTs shows excellent electrochemical durability at 10 mA cm −2 for 18 h. This work supplies a fresh strategy to design high-performance and cost-effective MoS2 -based catalysts for the HER.